Lactate attenuates PANoptosis and enhances ZBP-1 lactylation in macrophages in acute lung injury - Wang, Dan; Gong, Yi; Chen, Yehao; Wang, Zhefan; Yin, Jinxiang; Wang, Zhengrui; Yang, Xiao; Zhang, Yizhou; Huang, Jie; Jiang, Zhengyu (Frontiers in Immunology, 2025)
IntroductionAcute lung injury (ALI), characterized by excessive inflammation and cell death, is closely associated with ZBP1-mediated PANoptosis, a programmed cell death mechanism. The intrinsic regulatory mechanism of PANoptosis remains poorly investigated.MethodsIn this study, we investigated the protective effects of lactate on lipopolysaccharide (LPS)-induced ALI and its potential regulatory role in ZBP1-mediated PANoptosis.ResultsOur results showed that lactate effectively reduced inflammatory cytokine (TNF-α, IL-6, and IL-1β) and CD11b+Gr1+ monocyte infiltration in bronchoalveolar lavage fluid and serum. It also alleviated lung pathology and suppressed PANoptosis markers (cleaved caspase-1, GSDMD-p20, phospho-MLKL, and cleaved caspase-3/8). Mechanistically, lactate decreased ZBP1 expression and its interaction with RIPK1 and TRIF while enhancing ZBP1 lactylation. Notably, the ZBP1 agonist CBL0137 reversed the protective effects of lactate. In vitro experiments demonstrated that lactate inhibited LPS + 5z7-induced PANoptosis in macrophages by reducing the ZBP1-RIPK1-TRIF interaction and promoting ZBP1 lactylation, which was dependent on MCT1. Thus, our study demonstrated that lactate attenuates ALI by suppressing ZBP1-mediated PANoptosis, possibly through Mct1-related lactylation.ConclusionThe present study revealed the regulatory role of lactate in inflammation and cell death in ALI and suggested a lactylation-associated therapeutic strategy for ALI.